THE EFFECT OF HEDONIC AND UTILITARIAN MOTIVATION ON CUSTOMER SATISFACTION AMONG NETFLIX USERS IN BANDUNG CITY - Nabil Ahnaf Rustiana; R. Ela Sulastri; Farid Arifin (Asosiasi Dosen Muda Indonesia, 2026)
The rapid development of the digital streaming industry compels platforms such as Netflix to continuously enhance user satisfaction amid intensifying competition. This study aims to analyze the conditions of Hedonic Motivation, Utilitarian Motivation, and Customer Satisfaction among Netflix users in Bandung City, and to examine the influence of Hedonic Motivation and Utilitarian Motivation on Customer Satisfaction both partially and simultaneously. A descriptive and verificative research method with a quantitative approach was applied. The sample consisted of 100 Netflix users in Bandung City, selected through purposive sampling based on the Lemeshow formula. Data were analyzed using path analysis with data transformation performed through the Method of Successive Interval (MSI). The results indicate that Hedonic Motivation and Utilitarian Motivation are both in the